2008
DOI: 10.2174/1874828700801010001
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Hypercoagulability in Sepsis Using ROTEM® Thromboelastometry: A Case Series

Abstract: This case series presents three patients with sepsis/septic shock in whom standard coagulation tests (international normalized ratio, activated partial thromboplastin time, fibrinogen, antithrombin, thrombocytes) and ROTEM ® thromboelastometry (InTEM, ExTEM, FibTEM) were simultaneously performed. Although all patients showed significantly prolonged plasmatic coagulation times with a putatively increased risk of bleeding, ROTEM ® thromboelastometry revealed normal clotting times and even signs of hypercoagulabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
1
2
0
1
Order By: Relevance
“…Similar changes in clot formation, which were accompanied by a decrease in plasma fibrinogen level, have been shown in rats 6 h after endotoxin administration [26,27]. The decrease in hemostatic potential in the animal models reported here and elsewhere is in contrast to data obtained in clinical studies where sepsis, at least in its early state, was associated with hypercoagulability with an increase in clot formation rate and maximum clot firmness [28][29][30]. Thus, the question arises as to whether sepsis in rodents does not result in hypercoagulability, or whether hypercoagulability quickly switches to a hypocoagulable state owing to consumption of clotting factors.…”
Section: Discussionsupporting
confidence: 85%
“…Similar changes in clot formation, which were accompanied by a decrease in plasma fibrinogen level, have been shown in rats 6 h after endotoxin administration [26,27]. The decrease in hemostatic potential in the animal models reported here and elsewhere is in contrast to data obtained in clinical studies where sepsis, at least in its early state, was associated with hypercoagulability with an increase in clot formation rate and maximum clot firmness [28][29][30]. Thus, the question arises as to whether sepsis in rodents does not result in hypercoagulability, or whether hypercoagulability quickly switches to a hypocoagulable state owing to consumption of clotting factors.…”
Section: Discussionsupporting
confidence: 85%
“…However, TEG was suggestive of hypercoagulability in these patients and surgery could be performed with minimal blood loss. [ 15 ] Sivula et al in 2009 assessed the role of thromboelastometry in severe sepsis and found a trend towards hypercoagulability in patients without DIC and a trend towards hypocoagulability in those with overt DIC. [ 16 ] The initial phase of sepsis is characterized by the formation of microvascular thrombi and the later phase manifests as a hypocoagulant phase secondary to consumptive coagulopathy.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that sepsis, at least in its early state, was associated with hypercoagulability, indicated in particular by an increase in CFR and MCF [14,15]. Thus, the question arises of whether endotoxinemia and/or sepsis in mice and rat models do not result in hypercoagulability or whether hypercoagulability quickly switches to hypocoagulability, owing to consumption of hemostatic factors.…”
mentioning
confidence: 99%